Chlorobiphenyls (PCB) and PAHs in water masses of the northern North Atlantic - Schulz-Bull, Detlef E.; Petrick, Gert; Bruhn, Regina; Duinker, Jan C. (Marine Chemistry, 1998)
Concentrations of 23 individual chlorobiphenyls (CBs) and 6 polyaromatic hydrocarbons (PAHs) were determined in different water masses of the North Atlantic Ocean around Iceland. The study was carried out in the framework of the second Intergovernmental Oceanographic Commission (IOC) baseline studies of contaminants in the North Atlantic Ocean, involving trace organics and trace elements. Concentrations of individual CBs were extremely low. In solution, they varied between <2 and 126 fg dm−3 and in suspension between <2 and 1400 fg dm−3. The values for their sum (∑CB) were between 10 and 1048 in solution, and 286–11 241 fg dm−3 in suspension. ∑PAHs were present in the <5–65 pg dm−3 range, p,p′-DDE and hexachlorobenzene were <2 fg dm−3. The concentrations of CBs and PAHs decreased from the surface towards the bottom at each station. The lowest concentrations were found in Norwegian Sea Deep Water (∑CB 10 fg dm−3), concurrent with the lowest halocarbon concentrations found during the cruise. Values in near-surface waters were considerably lower than those determined at mid-latitudes of the North Atlantic. These findings reflect the mixing of water bodies with higher CB concentrations from the central North Atlantic with less contaminated waters from the Arctic Ocean. Concentrations in suspension exceeded those in solution in most samples, as a result of the relatively high suspended matter concentrations in the waters around Iceland. Particulate CB and PAH concentrations were positively correlated with particulate organic carbon concentrations. This suggests that suspended organic material is a carrier for these relatively apolar organic compounds in the water column. The data do not support the co-distillation concept suggested in the literature.